Value of Isolated IgA Anti–β2‐Glycoprotein I Positivity in the Diagnosis of the Antiphospholipid Syndrome. Issue 12 (27th November 2013) - Murthy, Vijaya; Willis, Rohan; Romay‐Penabad, Zurina; Ruiz‐Limón, Patricia; Martínez‐Martínez, Laura A.; Jatwani, Shraddha; Jajoria, Praveen; Seif, Alan; Alarcón, Graciela S.; Papalardo, Elizabeth; Liu, Jigna; Vilá, Luis M.; et al.
Abstract : Objective: To examine the prevalence of isolated IgA anti–β2 ‐glycoprotein I (anti‐β2 GPI) positivity and the association of these antibodies, and a subgroup that bind specifically to domain IV/V of β2 GPI, with clinical manifestations of the antiphospholipid syndrome (APS) in 3 patient groups and to evaluate the pathogenicity of IgA anti‐β2 GPI in a mouse model of thrombosis. Methods: Patients with systemic lupus erythematosus (SLE) from a multiethnic, multicenter cohort (LUpus in MInorities, NAture versus nurture [LUMINA]) (n = 558), patients with SLE from the Hopkins Lupus Cohort (n = 215), and serum samples referred to the Antiphospholipid Standardization Laboratory (APLS) (n = 5, 098) were evaluated. IgA anti‐β2 GPI titers and binding to domain IV/V of β2 GPI were examined by enzyme‐linked immunosorbent assay (ELISA). CD1 mice were inoculated with purified IgA anti‐β2 GPI antibodies, and surgical procedures and ELISAs were performed to evaluate thrombus development and tissue factor (TF) activity. Results: A total of 198 patients were found to be positive for IgA anti‐β2 GPI isotype, and 57 patients were positive exclusively for IgA anti‐β2 GPI antibodies. Of these, 13 of 23 patients (56.5%) in the LUMINA cohort, 17 of 17 patients (100%) in the Hopkins cohort, and 10 of 17 patients (58.9%) referred to APLS had at least one APS‐related clinical manifestation. Fifty‐four percent of all the IgA anti‐β2 GPI–positive serum samples reacted with domain IV/V of anti‐β2 GPI, and 77% of those had clinical features of APS. Isolated IgA anti‐β2 GPI positivity was associated with an increased risk of arterial thrombosis ( P < 0.001), venous thrombosis ( P = 0.015), and all thrombosis ( P < 0.001). The association between isolated IgA anti‐β2 GPI and arterial thrombosis ( P = 0.0003) and all thrombosis ( P = 0.0003) remained significant after adjusting for other risk factors for thrombosis. In vivo mouse studies demonstrated that IgA anti‐β2 GPI antibodies induced significantly larger thrombi and higher TF levels compared to controls. Conclusion: Isolated IgA anti‐β2 GPI–positive titers may identify additional patients with clinical features of APS. Testing for these antibodies when other antiphospholipid tests are negative and APS is suspected is recommended. IgA anti‐β2 GPI antibodies directed to domain IV/V of β2 GPI represent an important subgroup of clinically relevant antiphospholipids.